UKURAN PERUSAHAAN DAN PROFITABILITAS SEBAGAI PENENTU FINANCIAL DISTRESS: Studi Empiris Pada Perusahaan Manufaktur Kosmetik Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2023 - Ferdinandus, Stenly Jacobus; Kamarudin, Kamalia; Josef Richy Pattiruhu (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
This study uses company size and profitability as its independent variables because these two variables are expected to produce data that is accurate enough to provide an overview of the company's potential to experience financial distress. This study aims to determine and analyse the effect of company size on financial distress, to determine and analyse the effect of profitability on financial distress. In addition, to determine and analyse the effect of company size and profitability on financial distress. The data analysis technique uses a panel data regression model which is processed using the E-Views 12 Student Version application. The results of this study indicate that: (1) Company size has no effect on financial distress. (2) Profitability affects financial distress. (3) Company size and profitability simultaneously affect financial distress. The t test results on the Company Size variable (X1) obtained a tcount value of 0.0427 < t table, namely 1.69 and a significance value of 0.96> 0.05 so that Ha is rejected and H0 is accepted. The results of the t test on the Profitability variable obtained atcount value of 3.6654> than the t table which is 1.69 and the prob value. 0.00 <0.05. Therefore, Ha is accepted and H0 is rejected. The F test results show that simultaneously, the Company Size and Profitability variables have a significant effect on Financial Distress. The Fcount value of 4.83>Ftable is 2.85 and the probability value is 0.00 <0.05 so that Ha is accepted and H0 is rejected.